Organoleptic Analysis Of The Honeycomb Cake (Kue Sarang Semut) - Faridah, Anni; Jannah, Raudhatul; Marlis, Merisa (Food Science and Technology Journal (Foodscitech), 2020)
The Honeycomb Cake or Caramel Cake or widely known in Indonesia as "Kue Sarang Semut" is a type of cake that preferred by many people and has a distinct colour, texture and aroma. Some of its main ingredients are caramel and wheat flour. But the caramel-making is generally sugarcane-based, and the flour is still usually from wheat, which its availability is always depended on import traffic and its import activity is now increasing. Therefore, it is necessary to research the cake's organoleptic test using different types of sugar and the flour substitution of tofu dregs. This research is classified as a pure experiment and conducted in two stages and uses Completely Randomised Design, which is consisted of four treatments. The first stage uses four different types of sugar (granulated sugarcane, aren sugar, palm sugar, and rock sugar) and the second stage is four types of tofu dregs flour amount (0%, 15%, 30%, and 45%) used, with three-time repetition. The obtained data later tabulated into a table and will be examined using Analysis of Variance test. If there is any significant difference, the Duncan test will then applied. This research concludes that the different types of sugar significantly affect the colour and aroma quality. Furthermore, the amount of the wheat flour substitute of tofu dregs flour significantly affect the volume, colour, aroma, chewiness texture, hollow texture, and taste satisfaction. The best treatment of the Honeycomb Cake is obtained from the usage of pam sugar and 15% amount of tofu dregs flour.